PKM Kelompok Pengerajin Bakol Berbasis E-Commerce di Era Pandemi Covid: PKM Group of Craftsman Bakol Base on E- Commerce in the Era of the Covid Pandemic - Hazilina, Hazilina; Suryadi, Edy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
A group of basket-woven craftsmen in Sungai Belidak Village, Sungai Kakap District, Kubu Raya Regency is community group located on Jl.H.Djelai RT.16 RW.01. This group has been running for two years and can increase women’s income in the neighborhood by around 68% percent of the previous family income. The problem this group faces is from the marketing aspect is still using personal communication so that the product is still dependent on the order. Currently, the basket craftsman group has a market share of catering which during the pandemic, many of these businesses did not carry out their activities, causing sales from these baskets to drop drastically by 80% before the covid-19 pandemic; business management that is not yet running. So far, it has never been documented in the form of bookkeeping regarding business management that partners do so that the results have not been maximally obtained; as well as aspects of legality; parts of design management that partners control are still few, only one design/motif is being worked on; Branding is still weak. The method used is mentoring and training. The results obtained from the implementation of service are increased knowledge and skills of partners in managing digital-based craft businesses during the pandemic, transfer of science and technology to partners in the form of website creation, social media accounts, and online stores in the marketplace, transfer of technology to partners in the form of business management assistance and training, transfer of technology to partners in the form of product branding.